Conditional survival and recurrence of remnant gastric cancer after surgical resection: A multi‐institutional study. Issue 2 (26th December 2019) - Chen, Qi‐Yue; Zhong, Qing; Zhou, Jun‐Feng; Qiu, Xian‐Tu; Dang, Xue‐Yi; Cai, Li‐Sheng; Su, Guo‐Qiang; Xu, Dong‐Bo; Lin, Guang‐Tan; Guo, Kai‐Qing; Liu, Zhi‐Yu; Chen, Qiu‐Xian; et al.
Abstract: The present study was designed to evaluate the dynamic survival and recurrence of remnant gastric cancer (RGC) after radical resection and to provide a reference for the development of personalized follow‐up strategies. A total of 298 patients were analyzed for their 3‐year conditional overall survival (COS3), 3‐year conditional disease‐specific survival (CDSS3), corresponding recurrence and pattern changes, and associated risk factors. The 5‐year overall survival (OS) and the 5‐year disease‐specific survival (DSS) of the entire cohort were 41.2% and 45.8%, respectively. The COS3 and CDDS3 of RGC patients who survived for 5 years were 84.0% and 89.8%, respectively. The conditional survival in patients with unfavorable prognostic characteristics showed greater growth over time than in those with favorable prognostic characteristics (eg, COS3, ≥T3: 46.4%‐83.0%, Δ36.6% vs ≤T2: 82.4%‐85.7%, Δ3.3%; P < 0.001). Most recurrences (93.5%) occurred in the first 3 years after surgery. The American Joint Committee on Cancer (AJCC) stage was the only factor that affected recurrence. Time‐dependent Cox regression showed that for both OS and DSS, after 4 years of survival, the common prognostic factors that were initially judged lost their ability to predict survival ( P > 0.05). Time‐dependent logistic regression analysis showed that the AJCC stage independently affected recurrence within 2 years after surgery ( P < 0.05). A postoperative follow‐up model was developed for RGC patients. In conclusion, patients with RGC usually have a high likelihood of death or recurrence within 3 years after radical surgery. We developed a postoperative follow‐up model for RGC patients of different stages, which may affect the design of future clinical trials. Abstract : Patients with RGC usually have a high likelihood of death or recurrence within 3 years after radical surgery. We developed a postoperative follow‐up model for RGC patients of different stages.